Counseling to Prevent Stunting from an Early Age with Tulung Village Cadres, Kedamean District, Gresik Regency - Setiyawan, Agusti Adi; Devi, Ratna Sari; Bidayatul H, Aprilia Ristiawati (Journal of Health Community Service, 2023)
The problem of stunting is one of the nutrition problems that the Government of Indonesia focuses on, stunting is a nutritional status based on the PB/U or TB/U index where in the anthropometric standard for assesing children’s nutritional status, the result of the measurement are at the threshold (Z-Score) of <-2 SD to -3 SD (short) and <-3 SD (very short). The purpose of this study is to find out the understanding of Tulung Village cadre mothers about stunting in children. The design of this study uses observational with a crosssectional method with a population of 30 cadre mothers from Tulung village. The results of this study showed that the results of the Pre-Test obtained information that participants obtained a score of 60 (13.33%). The results of the pre-test assessment generally identified that there were still participants who did not understand stunting. Distribution of Respondents Based on the results of the Post Test, information was obtained that there was an increase in knowledge after stunting counseling (96.67%) and the lowest score of the posttest (3.33%). This indicates that there has been an increase in better knowledge after the implementation of counseling.